Self-help: What future role in health care for low and middle-income countries? - KR Nayar, Catherine Kyobutungi and Oliver Razum (International Journal for Equity in Health 2004, 3, 2004)
In the debate on 'Third options' for health care delivery in low- and middle-income countries it is proposed that self-help should play a larger role. Self-help is expected to contribute towards improving population health outcomes and reducing government health care expenditure. We review scope and limitations of self-help groups in Europe and South Asia and assess their potential role in health care within the context of health sector reform. Self-help groups are voluntary unions of peers, formed for mutual assistance in accomplishing a health-related purpose. In Europe, self-help groups developed out of dissatisfaction with a depersonalised health care system. They successfully complement existing social and health services but cannot be instrumentalized to improve health outcomes while reducing health expenditure. In South Asia, with its hierarchical society, instrumental approaches towards self-help prevail in Non-governmental Organizations and government. The utility of this approach is limited as selfhelp groups are unlikely to be sustainable and effective when steered from outside. Self-help groups are typical for individualistic societies with developed health care systems - they are less suitable for hierarchical societies with unmet demand for regulated health care. We conclude that self-help groups can help to achieve some degree of synergy between health care providers and users but cannot be prescribed to partially replace government health services in low-income countries, thereby reducing health care expenditure and ensuring equity in health care.